FINANCIAL INSTITUTIONS IN THE LEGAL SYSTEM OF ISLAMIC BANKING AND LEGAL DISPUTE SETTLEMENT - Akhmad Khisni (UNISSULA, 2018)
Islamic financial institutions in Indonesia are legalized in the governance of the banking law and in case of legal disputes become the absolute authority of the Religious Courts. Religious Courts readiness in responding to the development Islamic economics and resolve legal disputes are inevitable in the conduct of religious courts function as a legal institution, namely enforcement of certainty (juridical aspects) and justice (philosophical aspect), in addition to running the social aspects (sociological aspect). The position of Justice of religion as a social institution is dynamic, because of the exchange with the community dynamics that require the judge to explore, and understand the value of the law who live in the society. The implementation of Act No.3 of 2006 as amended by Act No. 50 Of 2009 regarding the Second Amendment to Act No.7 of 1989 concerning the Religious Courts, reinforced by Act No. 21 of 2008 concerning Islamic Banking. Institutional constraints faced by the Religious Court in handling cases Islamic economics is the law enforcement factors, factors of infrastructure, the judge in the religious courts appeared to be not effective due to the number of judges who have not been certified Islamic economy is still lacking, and the lack of educational and training of human resource development. In a more holistic approach to address the above problems, it is necessary reconstruction of the arrangement of the legal system and legal institutions and legal culture arrangement